Development of Android-Based Electronic Fuel Injection (EFI) System Learning Media - Supriyanto, Sidiq; Rohmantoro, Didik (Politeknik Piksi Ganesha Indonesia, 2024)
This study aims to: (1) Develop Android-based learning media for the Electronic Fuel Injection (EFI) system, (2) Determine the feasibility of this learning media, and (3) Assess students' responses to the learning media. This research uses the Borg and Gall model development method modified by Sugiyono with ten steps starting from problem identification to mass production. Data were collected using questionnaires and analyzed by descriptive quantitative methods. The results of the study show that this learning media is very feasible and useful based on evaluation scores from material experts, media experts, and student responses.